Editorial: The Rise of Interdisciplinarity - Pun, Min (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
DOI: http://dx.doi.org/10.3126/ctbijis.v1i1.10462 Crossing the Border: International Journal of Interdisciplinary Studies Vol.1(1) 2013